1998
DOI: 10.1016/s0895-7061(98)00095-8
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal angiotensin II directly influences central nervous regulation of blood pressure

Abstract: Intranasal administration of some peptides has been shown to directly influence central nervous functions, thus pointing to a nose-brain pathway for these substances in humans. The present study investigated whether intranasal administration of angiotensin II (ANG II) affects central nervous functions of cardiovascular control in a different way from intravenously administered ANG II. In a balanced cross-over design 12 healthy men were treated with ANG II intravenously (2.5 g), ANG II intranasally (400 g), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…The results indicated that a direct pathway from nose to brain existed. Derad et al (1998) evaluated the effect of angiotensin II on the central nervous functions of cardiovascular control after nasal and intravenous administration in 12 volunteers in a balanced cross-over design study. For intravenous and nasal administration of angiotensin II similar plasma levels were seen and both methods of administration resulted in comparable acute raises in blood pressure.…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that a direct pathway from nose to brain existed. Derad et al (1998) evaluated the effect of angiotensin II on the central nervous functions of cardiovascular control after nasal and intravenous administration in 12 volunteers in a balanced cross-over design study. For intravenous and nasal administration of angiotensin II similar plasma levels were seen and both methods of administration resulted in comparable acute raises in blood pressure.…”
Section: Human Studiesmentioning
confidence: 99%
“…); Adrenocorticotropin 4±10 (nˆ54) (Derad et al 1998); Insulin (nˆ12) ; Diazepam ((nˆ8) ? (Lindhardt et al 2001).…”
Section: Ratunclassified
“…28,32 In addition, the interaction between the renin-angiotensin system and the sympathetic nervous system might be mediated through central AT 1 receptors in the brain. [33][34][35] (4) Facilitation of norepinephrine release by presynaptic AT 1 -receptor activation might be counteracted by presynaptic AT 1 receptors, which can inhibit norepinephrine release and are downregulated in cardiomyocytes of patients with chronic heart failure. 22,23,36 …”
Section: Intracoronary Angiotensin II Infusion and Norepinephrine Relmentioning
confidence: 99%
“…The dosing of ANGII was adopted from a previous study of ours establishing dose-response curves for the effects of ANGII on blood pressure and for blood ANGII concentrations, which revealed that the intranasal administration of 400 μg ANGII and the intravenous infusion of 2.5 μg ANGII led to equivalent blood ANGII concentrations. 30 Before each test session, the AT1 receptor blocker valsartan (80 mg) was administered orally twice (12 and 6 hours before the intranasal substance), and blood pressure was controlled by oscillometric measurements at the upper arm to adjust and control continuous blood pressure recording via the 2-finger Portapress system (model 2 with a height correction system, TNO Institute of Applied Physics). Measurements switched automatically from one finger to the other after 30-minute periods.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…In a previous study, we found that the intranasal administration of ANGII in humans induced the release of vasopressin, whereas the prolonged neurogenic blood pressure increase was blocked. 30 Those findings led us to suspect that within the brain, ANGII might act to decrease blood pressure, although such an effect was masked in that study because of ANGII that, after intranasal administration, spilled over into the bloodstream to activate angiotensin receptors in the circumventricular organs. With this knowledge, the present study aimed to investigate whether intranasal ANGII reduces blood pressure in healthy humans, whereas any afferent angiotensinergic effects via the blood were selectively blocked by the AT1 receptor blocker valsartan.…”
mentioning
confidence: 95%